Achieving higher hierarchical structures by cooperative assembly of tripeptides with reverse sequences. Issue 16 (5th April 2023) - Wang, Zhongyan; Shang, Yuna; Luo, Hongjing; Yang, Cuihong; Yang, Zhimou; Ren, Chunhua; Liu, Jianfeng
Abstract : We report a novel strategy for achieving low-to-high hierarchical structure transformation through the cooperative self-assembly of naphthyl-capped tripeptides with reverse sequences. Abstract : Hierarchical self-assembly based on peptides in nature is a multi-component interaction process, providing a broad platform for various bionanotechnological applications. However, the study of controlling the hierarchical structure transformation via the cooperation rules of different sequences is still rarely reported. Herein, we report a novel strategy of achieving higher hierarchical structures through cooperative self-assembly of hydrophobic tripeptides with reverse sequences. We unexpectedly found that Nap-FVY and its reverse sequence Nap-YVF self-assembled into nanospheres, respectively, while their mixture formed nanofibers, obviously exhibiting a low-to-high hierarchical structure transformation. Further, this phenomenon was demonstrated by the other two collocations. The cooperation of Nap-VYF and Nap-FYV afforded the transformation from nanofibers to twisted nanoribbons, and the cooperation of Nap-VFY and Nap-YFV realized the transformation from nanoribbons to nanotubes. The reason may be that the cooperative systems in the anti-parallel β-sheet conformation created more hydrogen bond interactions and in-register π–π stacking, promoting a more compact molecular arrangement. This work provides a handy approach for controlled hierarchical assembly and the development of various functional bionanomaterials.